A population pharmacokinetic study of benzathine benzylpenicillin G administration in children and adolescents with rheumatic heart disease: new insights for improved secondary prophylaxis strategies. (15th April 2019) - Hand, Robert M; Salman, Sam; Newall, Nelly; Vine, Julie; Page-Sharp, Madhu; Bowen, Asha C; Gray, Katherine; Baker, Amy; Kado, Joseph; Joseph, John; Marsh, Julie; Ramsay, James; et al.
Abstract: Background: Benzathine benzylpenicillin G (BPG) is recommended as secondary prophylaxis to prevent recurrence of acute rheumatic fever and subsequent rheumatic heart disease (RHD). Following intramuscular injection, BPG is hydrolysed to benzylpenicillin. Little is known of the pharmacokinetics of benzylpenicillin following BPG in populations at risk of RHD. Methods: We conducted a longitudinal pharmacokinetic study of children and adolescents receiving secondary prophylaxis throughout six monthly cycles of BPG. Dried blood spot samples were assayed with LC-MS/MS. Benzylpenicillin concentrations were analysed using non-linear mixed-effects modelling with subsequent simulations based on published BMI-for-age and weight-for-age data. Results: Eighteen participants contributed 256 concentrations for analysis. None had benzylpenicillin concentrations >0.02 mg/L for the full time between doses. The median duration above this target was 9.8 days for those with a lower BMI (<25 kg/m 2 ), who also had lower weights, and 0 days for those with a higher BMI (≥25 kg/m 2 ). Although fat-free mass was a key determinant of benzylpenicillin exposure after a standard dose of BPG, having a higher BMI influenced absorption and almost doubled (increase of 86%) the observed t ½ . Conclusions: Few children and adolescents receiving BPG as secondary prophylaxis will achieve concentrations >0.02 mg/L for the majority of the time between injections. The discordance of this observation with reported efficacy of BPG to prevent rheumatic fever implies a major knowledge gap relating to pharmacokinetic/pharmacodynamic relationships between benzylpenicillin exposure and clinical outcomes.